Assessing Impact of Turmeric and Ginger Nanoemulsions Incorporated Carboxy Methyl Cellulose Edible Films on Storage of Refrigerated Chicken Meat Nuggets - Roshni; Nagamallika, E; Rao, B Eswara; Srinivasarao , T (Journal of Meat Science, 2024)
The study assessed the effectiveness of carboxymethyl cellulose (CMC) based films combined with nano-emulsions of turmeric (NTE) and ginger (NGE) in preserving and extending the shelf life of chicken nuggets when stored at 4°C for a 20-day period. The films contained 6% turmeric nanoemulsion (NTE) and 1% ginger nanoemulsion (NGE). Various parameters including microbial factors (total plate count, yeast and mould count, and psychrotrophic count), physicochemical properties (pH, 2-thiobarbituric acid, and cooking loss), and sensory attributes of the packaged chicken nugget samples were evaluated every 4 days interval. Results indicated that chicken nuggets packaged with CMC films containing nanoemulsions exhibited significantly lower microbial growth, improved physicochemical characteristics, and higher sensory scores compared to the control samples (P<0.05)